Incidence of neuromyelitis optica spectrum disorder (NMOSD) in China: A national population-based study - De-Cai Tian; Zixiao Li; Meng Yuan; Chengyi Zhang; Hongqiu Gu; Yongjun Wang; Fu-Dong Shi (Elsevier, 2020)
Background: Neuromyelitis Optica Spectrum Disorder (NMOSD) is an inflammatory disease of the central nervous system with preferential involvement of the optic nerve and spinal cord. However, data on NMOSD incidences in China, a country encompassing 20% of the world's population and covering vast areas of Eastern Asia, are unknown. Methods: We conducted the first nationwide survey of NMOSD, based on the database of the National Hospital Quality Monitoring System (HQMS) of China, which covers all 1665 tertiary hospitals. The "Medical Record Homepage" of all patients were consistently collected via a standard protocol across each tertiary hospital. The primary outcome was the incidence of NMOSD, diagnosed according to the 2015 International Panel for Neuromyelitis Optica Diagnosis criteria and identified by ICD-10 code (G36•0). Burden of hospitalization, comorbidities, and death were also evaluated. Findings: We identified 33,489 hospital admissions for 17,416 NMOSD diagnosed patients from 2016 to 2018. 11,973 patients were newly diagnosed NMOSD. The age and sex adjusted incidence per 100,000 person years was 0•278 (95% confidence interval [CI], 0•273-0•283), with 0•075 (0•069-0•08) in child and 0•347 (0•34-0•353) in adult. The peak age of onset NMOSD is 45-65 years with an incidence 0•445/100,000 (95% CI, 0•433-0•457). The female to male ratio was 4•71 (p<0•001, 95% CI, 4•50-4•94). Geographical distribution of NMOSD is not related to the latitude gradient. Sjögren's syndrome (1,124/17,416, 6•5%) and systemic lupus erythematosus (387/17,416, 2•2%) are the most frequently autoimmune comorbidities. 106 adults and 4 children of the 17,416 NMOSD cohort died. Interpretation: The incidence of NMOSD in China per 100,000 person years was 0•278, with 0•075 in child and 0•347 in adult. The geographical distribution of NMOSD is not related to the latitude gradient. Funding: National Science Foundation of China (91949208, 91642205, and 81830038); Advanced Innovation Center for Human Brain Protection, Capital Medical University, Beijing.